THE BENEFITS AND CHALLENGES OF SKILLS DEVELOPMENT AND THEIR IMPACTS WITHIN CONTEMPORARY COMPANIES - Cardoso, Bruna Mota; da Costa, Elvio Carlos; Costa, Andressa Bregantin Elias (Revista Interface Tecnológica, 2023)
This article aimed to identify the benefits of skills development and its impacts within contemporary companies, in order to identify which actions are necessary to obtain a better development of skills, hard and soft Skills required by the competitive labor market. It is emphasized the importance of managers and employees to develop these skills, as they are differentiating during the recruitment and selection process. Methodologically the present work was developed, based on a bibliographic survey, through scientific articles, and a research that was applied through a questionnaire, composed of 10 closed and open questions, and 14 people answered. The results indicate that the vast majority of participants know how to differentiate the terms studied in this article and understand the importance of competencies and skills within and outside organizations. Therefore, the development of skills provides benefits both for companies, especially regarding the culture of organizational learning, and for employees who get the possibility of professional growth and better productive performances.